2023
DOI: 10.3390/antibiotics12040691
|View full text |Cite
|
Sign up to set email alerts
|

Candida lipolytica Bloodstream Infection in an Adult Patient with COVID-19 and Alcohol Use Disorder: A Unique Case and a Systematic Review of the Literature

Abstract: Candida lipolytica is an uncommon Candida species causing invasive fungemia. This yeast is mainly associated with the colonisation of intravascular catheters, complicated intra-abdominal infections, and infections in the paediatric population. Here, we report a case of C. lipolytica bloodstream infection in a 53-year-old man. He was admitted for an alcohol withdrawal syndrome and mild COVID-19. Among the primary risk factors for candidemia, only the use of broad-spectrum antimicrobials was reported. The empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Stavrou et al [91] demonstrated that among twenty-seven Y. lipolytica isolates, 74.1% were resistant to echinocandins. In contrast, Yu et al [93] have not reported resistance strains of Y. lipolytica in their retrospective study, and the use of echinocandins in bloodstream infections due to Y. lipolytica had a favourable outcome [98]. Based on the literature, no data regarding the resistance mechanism for echinocandins are described for the S. ciferrii complex as well as for Y. lipolytica, but elevated echinocandin MICs have been associated with several single amino acid substitutions caused by mutations in specific "hot spot" regions of the well-conserved target genes FKS1 of Y. lipolytica [99].…”
Section: Treatment and Resistancementioning
confidence: 88%
“…Stavrou et al [91] demonstrated that among twenty-seven Y. lipolytica isolates, 74.1% were resistant to echinocandins. In contrast, Yu et al [93] have not reported resistance strains of Y. lipolytica in their retrospective study, and the use of echinocandins in bloodstream infections due to Y. lipolytica had a favourable outcome [98]. Based on the literature, no data regarding the resistance mechanism for echinocandins are described for the S. ciferrii complex as well as for Y. lipolytica, but elevated echinocandin MICs have been associated with several single amino acid substitutions caused by mutations in specific "hot spot" regions of the well-conserved target genes FKS1 of Y. lipolytica [99].…”
Section: Treatment and Resistancementioning
confidence: 88%
“…but the methods for species identification are not well described and the cases were also associated with predisposing factors in the patients, but they were not specified. Simonetti et al (2023) report a case of fungaemia caused by Y. lipolytica in a patient with predisposition factors, COVID-19 infection and a history of alcohol syndrome. The literature update did not identify any new information that would change the QPS status of Y. lipolytica.…”
Section: Yarrowia Lipolyticamentioning
confidence: 99%
“…Since three cases of eye infection caused by Y. lipolytica were reported in France in 1976, more than 30 relevant pathogenic studies and case reports have been published ( 4 12 ). Recently, Y. lipolytica has been reported to cause nosocomial outbreaks, foodborne infections, breakthrough fungemia, and catheter-related infections that may be complicated by septic shock in immunocompromised patients and even those co-infected with severe acute respiratory syndrome coronavirus 2 ( 4 , 9 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%